Mass transfer intensification strategies for liquid–liquid extraction with single drop investigations - Saien, Javad; Jafari, Farnaz (International journal of heat and mass transfer, 2019)
•Extraction with drops can be intensified by additives and adjusting operations.•Nanoparticles exhibit desired effects when added with specified concentrations into drops.•External fields can intensify the rate of mass transfer either with or without nanoparticles.•Retarding effect of nanoparticles in continuous phase can be compensated by external fields.•Recent investigations indicate promising results of ionic liquid solvents in drop dispersions. Process intensification of liquid–liquid extraction based on single drop studies is discussed. Design, simulation and optimization of this process, usually adopts with swarm of drops, and depends on individual drops behavior as well as the relevant influential parameters. Improving mass transfer performance with optimized operating conditions or using additives like salts and nanoparticles are distinctive concerns. Accordingly, as a systematic study, the hydrodynamic and mass transfer behavior of drops as well as effects of operating parameters are considered. Due to the importance of subject, the behavior of nanoparticles for improving extraction process, with or without external fields, is highly regarded. Furthermore, the promising techniques/materials of reactive extraction, microfluidic extraction, ionic liquid solvents, their combination and coupling heat and mass transfer are considered. The content will bring greater clarity to select additives and to employ suitable conditions. Indeed, drop intensification methods, in relation to the drop breakage/coalescence, build the high performance industrial scale operations.